Trends, collaboration, and thematic mapping of flipbooks in learning: A systematic review - Muhammad Syafrani Permadi; Irma Soraya; Moch. Chafiid Dhuha; Abdurrazaq Murtaja (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
Over the past two decades, flipbook-based learning has emerged as an innovative approach in instructional design, designed to accommodate the diverse needs of students. The present study employed the Systematic Literature Review (SLR) method, based on the PRISMA protocol, to identify, review, and evaluate relevant articles to address the research questions. The objective of this study was to analyse publication trends, collaboration patterns, and thematic mapping in studies on flipbook-based learning. The findings revealed that, of the 390 articles identified from the Scopus and DOAJ databases, 31 met the predefined inclusion and exclusion criteria. The findings indicate that research on flipbooks experienced a significant surge in 2024, followed by a decline in 2025 and 2026, likely influenced by the ongoing indexing process. However, during the 2023–2024 period, publication trends showed a substantial increase, corresponding to the post-pandemic recovery period when most learning activities were conducted online. In terms of collaboration, the research was predominantly conducted by Indonesian authors, with very limited international research networks. Meanwhile, the thematic mapping revealed that flipbook research focuses on the development of digital learning media aimed at improving the quality of student learning, particularly in terms of critical thinking and learning outcomes. In addition, most studies employed the Research and Development (R&D) approach.